Bladder perivascular epithelioid cell tumour and tuberous sclerosis complex: a rare association. Issue 5 (26th May 2021) - Tee, Jo Lin; Chambers, Jonathan; Strutton, Geoffrey
Abstract : Bladder perivascular epithelioid cell tumours (PEComas) associated with tuberous sclerosis complex (TSC) are rare, with only one other case report in the literature to date. We present our case of a bladder PEComa in a young adult female with TSC arising de novo. Histopathology showed features in keeping with an angiomyolipoma and confirmatory immunohistochemical stains were positive for both melanocytic and smooth muscle markers. She was well at the 6-month follow-up post-surgical resection. Given the rarity of such lesions in the bladder, we discuss the diagnostic and prognostic challenges, clinical implications and a brief review of the literature to date.